2019
DOI: 10.1016/j.jsv.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Model updating of uncertain parameters of carbon/epoxy composite plates from experimental modal data

Abstract: This work presents a methodology to obtain physically-sound models of composite structure laminates using a combination of modal analysis, numerical modelling and parameter updating, avoiding the common uncertainties on the constructions of similar numerical models. Moreover this model establishes the baseline (pristine situation) of the dynamic behaviour of the set of composite plates. Therefore it could be applied for condition assessment or quality manufacturing control of existing structures through a nond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…The smaller dimension of the element will coincide with the thickness of each of the 21 plies or 32 plies of the plates, that is, 0.19 mm. Regarding the larger dimension, a sensitivity analysis was carried out with values of the element size between 25 and 2.5 mm [18].…”
Section: Reference Fem Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The smaller dimension of the element will coincide with the thickness of each of the 21 plies or 32 plies of the plates, that is, 0.19 mm. Regarding the larger dimension, a sensitivity analysis was carried out with values of the element size between 25 and 2.5 mm [18].…”
Section: Reference Fem Modelmentioning
confidence: 99%
“…Thus, in the next step, the model updating, only the numerical values of those parameters that are identified to be influential will be adjusted until the objective function is minimized. The sensitivity analysis performed in this work is explained in detail in [18]. It was demonstrated that the three parameters to which the model is more sensitive, are those presented in Table 5.…”
Section: Vibration Measurements Using 3d Dicmentioning
confidence: 99%
See 1 more Smart Citation
“…The model updating is based on the experimental results, and the error between simulation and experimental results is minimized by adjusting the matrix or parameters appropriately to improve the model accuracy [4]. Currently, model updating methods are primarily categorized into direct updating and iterative updating [5].…”
Section: Introductionmentioning
confidence: 99%
“…Murray 7 presented the experimental verification of a composite FEM by static bending tests of 500 mm ×200 mm BT coupled laminate plates, it was found that the bending and twisting response of samples were linear within the range of applied loads and the sensitivity of laminate thickness and accuracy of ply angles. Cuadrado 8 presented a methodology to obtain a physically more accurate model using experimentally measured modal parameters. Thai 9 illustrated a new tangent shear deformation theory for the static free vibration and buckling analysis of laminated composite and sandwich plates, a weak form for the plates based on ITSDT was derived and solved using isogeometric analysis.…”
Section: Introductionmentioning
confidence: 99%